A study and shaping of a differential mobile robotic platform (2007)
It presents the study and shaping of a robotic differential platform and its configuration characteristics. In the dynamic model is included the study of two DC motors connected to every wheel as system actuators and there are analyzed kinetic equations with and without rubbing coefficients. It was decided a direct cinematic model and it is compared by simulations in the Matlab® with the models presented with the tool HEMERO.